New Regionalism in World Politics. Example of the United States of America in Conditions of Western Hemisphere - Pavel Neumann (Czech Journal of International Relations, 2004)
This article deals with regional integration agreements as one of the key tendencies of the international economic relations. Regionalism could be a way of the world trade liberalisation opening its multilateral form alternative. The U.S. started to emphasise the regional integration in the late 1980s. Nowadays, the reason for American approach is often said to be due to the competitive liberalisation strategy. Within the regional liberalisation, the important U.S. interests can be supported more efficiently than in its multilateral form. The establishment of NAFTA serves as an example in the North America. Nevertheless, further regional integration based on the FTAA completion is much more difficult as the NAFTA experience cannot be simply applied to other integration agreements. Concerning the U.S. approach, a conclusion can be drawn that despite their general acceptance of multilateralism the U.S. uses regional integration agreements pragmatically to compensate for the insufficiency of the multilateral liberalisation.